(untitled) (Swiss Medical Weekly, 2012)
Malignant hyperthermia (MH) is a subclinical myopathy, usually triggered by volatile anaesthetics and depolarising muscle relaxants. Clinical symptoms are variable, and the condition is sometimes difficult to identify. Nevertheless, rapid recognition and specific as well as symptomatic treatment are crucial to avoid a lethal outcome. Molecular genetic investigations have confirmed the skeletal muscle type ryanodine receptor to be the major MH locus with more than 70% of MH families carrying a mutation in this gene. There is no screening method to test for MH, as current tests are invasive (open muscle biopsy) or restricted to MH families with known MH-associated mutations (molecular genetic testing). The prevalence of the MH trait is unknown, because the clinical penetrance after contact with triggering agents is very variable. More recently, MH mutations have been associated with rhabdomyolysis following statin therapy or with non-pharmacological triggering, such as exertional heat stroke.